Corporation tax and investment - Stuart Adam; Isaac Delestre; Vedanth Nair (Institute for Fiscal Studies (IFS), 2022)
UK business investment is the lowest in the G7 and among the lowest in the developed world. Tax has a role to play in shaping investment incentives, and the UK's corporate tax system is one of extremes. While the rate of corporation tax (19%) is exceptionally low, UK investment allowances are amongst the developed world's least generous. As a result, effective tax rates in the UK (a measure which accounts for the generosity of allowances as well as the headline rate) are middling by international standards. But they vary hugely across different kinds of investment, favouring investment in some assets over others and encouraging borrowing to finance investment. In this chapter we look closely at the nature of these distortions. We consider how the large package of corporate tax reductions announced in the recent 'mini-Budget' is likely to shape incentives to invest and what balance it strikes between encouraging domestic investment and attracting profitable ventures from overseas. Finally, we consider the road ahead. We examine the likely impact of rising inflation and interest rates. We emphasise the importance of stability and of setting out a clear long-term plan. And we set out a case for genuine structural reform of corporation tax, which could address distortions to the allocation and financing of investment as well as its level.
Keywords: 330; Business and investment; Taxes and benefits; IFS Green Budget 2022; Corporate taxes; Tax; Public finance; Investment